ANJAK PIUTANG (FACTORING) SEBAGAI BENTUK AKAD MUAMALAH MODERN - Quran, Amanah Aida (el-Jizya: Jurnal Ekonomi Islam, 2017)
Abstract In business world, people always want to expedite the production of goods, so as to increase profits and accelerate capital turnover, which in turn will promote economic growth. The increase of social demand for consumer goods causes many companies prepare funds, taken from fund provider called factoring. Financial or fund provider is a business institution that deals with financing in the form of purchasing and taking over and handling short term receivables. This paper discusses the concept of factoring in the perspective of the economic Islamic law using hiwalah theory approach. In addition, this article explain the different concept of sharia and conventional factoring. Keywords: Factoring, Hiwalah, Islamic Economics.